Digitalization for sustainable maintenance services: A systematic literature review - Bishal Raj Karki; Jari Porras (Digital Business, 2021)
Purpose: Maintenance services have evolved hugely from an inevitable part of production as a failure fixing activity to an essential strategic element to accomplish several business objectives including profit making. With the growing maintenance service industries, sustainability has remained a challenge and have garnered a great deal of attention over the last two decades. Maintenance services' impact on sustainability is a known concern and almost all sustainability dimensions are affected either positively or negatively. The purpose of this paper is to review and discuss the related literature on different maintenance services and their impact on sustainability. Design/methodology/approach: This research aims to study these concepts (maintenance services, sustainability impact and digitalization) independently and in relation to each other through systematic literature review of high-quality articles, with a focus to understand the relation between maintenance and sustainability and depict the role of digitalization in achieving those sustainability goals. Findings: This study presented the trend and publications related to maintenance services and its sustainability impact throughout 2009 to 2020. Publications related to maintenance services and corresponding sustainability impact were analyzed as a problem space and publications related to digitalization were analyzed as a solution space. Based on the analysis, a discussion on digitalization of maintenance service was conducted to highlight possible benefits and improvements towards various sustainability impacts. Originality/value: Digitalization and digital technologies are evolving and advancing every day. It is still yet to be known, what role could digitalization play in the maintenance services' impact on sustainability. This paper contains a state of the art on publications and discussion related to the digitalization for sustainable maintenance services. It offers insights and information on the current body of knowledge to academics, researchers, practitioners, maintenance personnel, digital managers, development teams and stakeholders concerned with maintenance services.
Keywords: 650; Maintenance services; Digitalization; Sustainability impacts